A note on measures of human capital for immigrants: examining the American Community Survey and New Immigrant Survey - Randall K. Q. Akee; Mutlu Yuksel (Institute for the Study of Labor (IZA), 2008)
In this paper we examine whether where one acquires their human capital matters in earnings regressions. We focus on a nationally-representative US data set and find that there is little difference between a measure of total years of education and measures for US and foreign-based years of education. There is a large difference, however, in where total experience is acquired: US-based experience commands a higher return to wages and is statistically highly significant. The measures used in this analysis must be inferred based on the year of migration to the US. Using an immigrant-specific data set, the New Immigrant Survey which contains explicit information on the human capital acquired in the US and abroad, we confirm these results.
urn:nbn:de:101:1-2009010747
Keywords: I21; J24; J61; 330; Immigrants; schooling; rates of return; Migranten; Bildungsertrag; Humankapital; Bildungsniveau; USA